2014
DOI: 10.1038/cdd.2013.199
|View full text |Cite
|
Sign up to set email alerts
|

p63 is a prosurvival factor in the adult mammary gland during post-lactational involution, affecting PI-MECs and ErbB2 tumorigenesis

Abstract: In embryogenesis, p63 is essential to develop mammary glands. In the adult mammary gland, p63 is highly expressed in the basal cell layer that comprises myoepithelial and interspersed stem/progenitor cells, and has limited expression in luminal epithelial cells. In adult skin, p63 has a crucial role in the maintenance of epithelial stem cells. However, it is unclear whether p63 also has an equivalent role as a stem/progenitor cell factor in adult mammary epithelium. We show that p63 is essential in vivo for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
55
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(67 citation statements)
references
References 66 publications
8
55
1
1
Order By: Relevance
“…Within this type of colonies the stem cells subpopulation is reported to be present (Martignani et al, 2010;Prater et al, 2014). In addition to this test, we reported that after 35 days of culture a cell population capable of forming alveolar like-structures in vivo with cellular doublelayer and luminal antigens, such as K18 and EpCAM (if expressed at high levels) (Stingl et al, 2005), or basal, such as P63 (Yallowitz et al, 2014), is present as confirmed by xenografts in NOD-SCID mice. We also observed the presence in the lumen of regenerate structure the signal for protein milk indicating a proper polarization and functional activity.…”
Section: Discussionmentioning
confidence: 61%
“…Within this type of colonies the stem cells subpopulation is reported to be present (Martignani et al, 2010;Prater et al, 2014). In addition to this test, we reported that after 35 days of culture a cell population capable of forming alveolar like-structures in vivo with cellular doublelayer and luminal antigens, such as K18 and EpCAM (if expressed at high levels) (Stingl et al, 2005), or basal, such as P63 (Yallowitz et al, 2014), is present as confirmed by xenografts in NOD-SCID mice. We also observed the presence in the lumen of regenerate structure the signal for protein milk indicating a proper polarization and functional activity.…”
Section: Discussionmentioning
confidence: 61%
“…It has been proposed that DNp63 abundance must be decreased in stem cells to allow their activation and the subsequent maturation of mammary progenitors. In accordance with this model, DNp63 is enriched in normal human mammary stem cells, whereas DNp63 is low in abundance or absent in the progenitors (26,39,40). Chakrabarti and co-workers (26) showed that DNp63, but not TAp63, In epithelial selfrenewing tissues, stem cells divide infrequently to produce a stem cell daughter and a nonstem-committed progenitor cell (transit-amplifying cell).…”
Section: Mammary Glandmentioning
confidence: 56%
“…In the normal mammary gland, p63 is confined to the basal/myoepithelial compartment (36). DNp63 preserves the self-renewing capacity of mammary stem cells, partially by promoting their quiescent state (26,(37)(38)(39). DNp63 and TAp63 isoforms are present in mouse mammary stem and progenitor cells, respectively.…”
Section: Mammary Glandmentioning
confidence: 98%
“…3,6,14,38. We have previously investigated the molecular mechanism of Itch recognition for the p63 transcription factor 39 in particular, because this powerful transcription factor is crucial for the development of epithelia, 31,[40][41][42][43][44][45] it is involved in cancer, [46][47][48][49][50][51][52][53][54][55][56][57][58][59] and when it is mutated it causes severe genetic diseases.…”
Section: Introductionmentioning
confidence: 99%